Electrocortical correlations between pairs of isolated people: A reanalysis [version 1; referees: 2 approved] - Dean Radin (F1000Research, 2017)
A previously reported experiment collected electrocortical data recorded simultaneously in pairs of people separated by distance. Reanalysis of those data confirmed the presence of a time-synchronous, statistically significant correlation in brain electrical activity of these distant “sender-receiver” pairs. Given the sensory shielding employed in the original experiment to avoid mundane explanations for such a correlation, this outcome is suggestive of an anomalous intersubjective connection.